Firm-size and wages: a case study of the manufacturing sector in Zimbabwe - Kupeta, Tsungai (School of Economics, 2022)
It has long been argued in the mainstream literature that workers in large firms earn higher wages than those in smaller firms. This phenomenon is recognised as an important puzzle that explains wage disparities in labour markets. This thesis analyses the link between firm size and wages in the Zimbabwean manufacturing sector and it is structured around three main research questions: (1) What is the link between firm size and wages in the formal and informal manufacturing sector in Zimbabwe? (2) Is there a firm-size wage premium in the formal and informal manufacturing sector in Zimbabwe? (3) If yes, what are the sources of the firm-size wage premium? The analysis of the study draws on the Matched Employer-Employee manufacturing firm-level survey dataset for formal and informal sector firms and workers that was collected in 2015. Using this dataset, we are able to distinguish between theories that attribute wage disparities to worker heterogeneity and those that hypothesise the importance of firm heterogeneity, which advances the existing literature by including the informal sector and a developing country case. We then apply the Mincerian wage regression approach to determine the magnitude, significance, and sources, of the firm size-wage premium. We control for a variety of human capital, individual, job, and firm characteristics to determine the source of the firm size wage relationship. The empirical results indicate a positive and significant association between firm size and wages in both the formal and informal sectors, as theoretically expected. The firm-size premium is more nuanced in the informal sector. Human capital endowments are found to contribute to the firm size-wage relations, at least for the formal sector. Job characteristics did not explain major variation in firm-size wage relationships. Thus, apart from human capital characteristics, most theories cannot explain the wage premium received by large firms. The results further indicate that capital intensity and firm productivity are important in shaping the firm size wage premium, although they did not alter the size effect much.